KONSELING KELOMPOK DENGAN TEKNIK ACCEPTANCE COMMITMENT THERAPY (ACT) DALAM MENINGKATKAN KESEJAHTERAAN SPIRITUAL MAHASISWA - Meigo Anugra Jaya; Hartini Hartini; Rini Puspitasari (Tarbiyatuna Kajian Pendidikan Islam, 2024)
Spiritual well-being is a perspective that is felt in the quality of a person's relationship in four areas, namely the relationship with God, other people, nature and oneself. Students who have spiritual well-being and low spiritual experience experience a high level of distress. This can reduce concentration, reduce attention, hinder the decision-making process, and reduce students' ability to realize their goals, roles and functions as students. This study aims to determine the effect of group counseling services using the Acceptance and Commitment Therapy (ACT) technique on improving the spiritual welfare of Campus B Curup students at the Bengkulu Ministry of Health Polytechnic. This type of research is a quasi experimental design. The population in this study were students from Campus B Curup Poltekkes Bengkulu Ministry of Health with a sample of 60 people consisting of 30 people in the experimental group and 30 people in the control group with purposive sampling. The data collection technique uses the Spiritual Well-Being Scale (SWBS) instrument. Independent data analysis using the Mann Whitney Test. There was a significant difference in the group that received group counseling services using the ACT technique compared to the group that did not receive group counseling services (p = 0.040, Î± = 0.05). So it can be interpreted that there is an influence of group counseling with the ACT technique on improving the spiritual welfare of Campus B Curup students at the Bengkulu Ministry of Health Polytechnic.